THE INFLUENCE OF LEARNING STARTS WITH A QUESTION METHOD TOWARDS THE STUDENTS’ READING COMPREHENSION - Wilany, Eka (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of this research was to find out whether there was an influence of Learning Starts with a Question method towards the Students' Reading Comprehension. This research used experimental quantitative research. The data used in this research were obtained from students’ learning outcomes in the experimental class and control class. The test was in the form of multiple-choice questions and was carried out before and after being given different treatments in each sample class, which were chosen by using Simple Random Sampling technique. After the learning outcomes were obtained, the data were calculated using the statistical T-test (Independent Sample T-test) formula. The results showed that there was an influence of Learning Starts with a Question method towards the Students' Reading Comprehension. This can be seen in the calculation of hypothesis testing results, that Tcount > Ttable (2,870 > 2,012) with a significant level of 5%, furthermore it can be concluded that there was an influence of Learning Starts with a Question method towards the Students' Reading Comprehension.